2019
DOI: 10.1177/0363546519883246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Impairment on Outcomes in Patients With Prearthritic Hip Disorders: A Systematic Review and Meta-analysis

Abstract: Background: Recent studies have suggested that mental health disorders negatively affect postoperative outcomes in patients with femoroacetabular impingement (FAI). However, the outcome measures reported and the effect sizes have varied. Furthermore, it is unknown whether similar effects are present in young adults with other hip disorders such as acetabular dysplasia. Purpose: To synthesize current evidence regarding the effect of baseline psychological impairment on postintervention outcomes in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
0
35
2
Order By: Relevance
“…Mental health is an important determinant of pain and functional outcomes for individuals with FAIS. [13][14][15][16][17][18] Recent cohort studies of 500 and 688 patients, respectively, found self-reported depression and/or anxiety to be a predictor for not achieving acceptable sports function and for persistent postoperative pain 2-year posthip arthroscopy. 13,14 Additional psychosocial factors such as pain catastrophizing, self-efficacy, and kinesiophobia are key contributors to pain and functional outcomes in orthopedic conditions of the shoulder and knee.…”
mentioning
confidence: 99%
“…Mental health is an important determinant of pain and functional outcomes for individuals with FAIS. [13][14][15][16][17][18] Recent cohort studies of 500 and 688 patients, respectively, found self-reported depression and/or anxiety to be a predictor for not achieving acceptable sports function and for persistent postoperative pain 2-year posthip arthroscopy. 13,14 Additional psychosocial factors such as pain catastrophizing, self-efficacy, and kinesiophobia are key contributors to pain and functional outcomes in orthopedic conditions of the shoulder and knee.…”
mentioning
confidence: 99%
“…Patients with FAI who had a lower baseline psychological impairment were shown to have an inferior outcome compared with those who did not suffer from mental health disorders [ 12 ]. Similarly, Plinsinga et al concluded in their article that patients with persistent GTPS had greater psychological distress, physical impairments and poor health-related quality of life, which were associated with pain and disability [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…23 It is possible that the interplay between these two phenomena contributed to the trend of lower rates of self-reported behavioral health impairment reported in the athlete subgroup of our study. Nevertheless, baseline depression and anxiety are associated with worse pre- and postoperative hip function (specifically after hip arthroscopy), 9,46 so we still advocate for screening for current or prior psychological impairment. When appropriate, guiding affected patients to resources for behavioral health management can be incorporated as part of a conservative management plan or for preoperative optimization.…”
Section: Discussionmentioning
confidence: 99%